Pengelolaan, Peserta Didik Pengelolaan Sistem Penerimaan Peserta Didik Baru di SMP Negeri 1 Panyabungan: Studi Kasus dan Solusi, : Sistem Penerimaan Peserta Didik Baru di SMP Negeri 1 Panyabungan, Peran Stakeholder dalam Proses PPDB di SMP Negeri 1 Panyabungan, Peran Stakeholder dalam Proses PPDB di SMP Negeri 1 Panyabungan - Dandi, Muhammad; Nasution, Mursyidan Auliya (STAIN Madina Press, 2025)
This study aims to analyze the management system of the New Student Admission (PPDB) process at SMP Negeri 1 Panyabungan and propose solutions to enhance the effectiveness and transparency of student selection. A case study approach with a descriptive qualitative method was employed. Data were collected through interviews with the principal, PPDB committee members, and parents of prospective students, as well as documentation of procedures and selection results for the 2023/2024 academic year. The findings reveal that although the school has implemented an online-based admission system in accordance with government regulations, several challenges persist. These include limited public understanding of online registration procedures, inadequate technological access, and perceived unfairness in the zoning policy implementation. To address these issues, the study recommends strengthening public outreach through local media, providing a technology assistance center at the school, and developing transparency features such as real-time application tracking. With these improvements, the PPDB process at SMP Negeri 1 Panyabungan is expected to become more equitable, efficient, and accountable. This study offers practical insights for other schools facing similar challenges in transitioning to a digital-based student admission system.